Twisted - Anderson, Laurie Halse (New York : Viking, 2007)
After finally getting noticed by someone other than school bullies and his ever-angry father, seventeen-year-old Tyler enjoys his tough new reputation and the attentions of a popular girl, but when life starts to go bad again, he must choose between transforming himself or giving in to his destructive thoughts.
Keywords: Family problems -- Fiction; Interpersonal relations -- Fiction; High schools -- Fiction; Schools -- Fiction; Coming of age -- Fiction; Ohio -- Fiction